Additive, electrolyte and battery

By using pyridinium propane sulfonate as an additive in aqueous zinc batteries, an organic functional film layer is formed and cation diffusion is regulated, the problems of dendrites formation and hydrogen evolution reaction are solved, and the safety performance and service life of the battery are significantly improved.

CN119627257APending Publication Date: 2025-03-14THE HONG KONG POLYTECHNIC UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311188884.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing aqueous zinc batteries are prone to form dendrites during charging and discharging, resulting in low efficiency of Coulomb, fast capacity attenuation, and a risk of short circuit. The low redox potential of zinc will react with the electrolyte, further reducing efficiency.

Method used

The pyridinium propane sulfonate salt is used as an additive to form an organic functional film layer on the surface of the zinc negative electrode through it, preventing the contact between water molecules and the negative electrode in the electrolyte, regulating the cation diffusion mode, reducing dendrite formation, and complexing the sulfonate functional groups with zinc cations to weaken the side reaction.

Benefits of technology

It significantly improves the safety performance and service life of the battery, reduces hydrogen evolution corrosion and passivation reaction, reduces the formation and growth of dendrites, and thus improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627257A_ABST
    Figure CN119627257A_ABST
Patent Text Reader

Abstract

The invention discloses an additive, an electrolyte and a battery. The additive is pyridinium propane sulfonate. The additive provided by the invention can regulate and control the physicochemical properties of the electrolyte. At the interface of the zinc negative electrode and the electrolyte, polar functional groups pyridine and sulfonate ions are adsorbed on the surface of the negative electrode of the battery, so that on one hand, water molecules in the electrolyte can be prevented from being contacted with the zinc electrode, thereby inhibiting hydrogen evolution corrosion and passivation reaction caused by water decomposition; and on the other hand, the diffusion mode of zinc ions on the surface of the electrode can be regulated and controlled, and regular and compact electro-deposition of the zinc ions is induced, so that formation and growth of zinc dendrites are prevented at a relatively large probability. Meanwhile, sulfonate ions can be complexed with zinc ions, water molecules in solvation sheaths are eliminated, and the degree of side reaction is weakened. In conclusion, after the additive is used, the performance of the battery is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery electrolytes, and specifically relates to an additive, an electrolyte having the additive, and a battery having the electrolyte. Background Art

[0002] Energy crisis and environmental pollution caused by excessive use of fossil fuels are issues of continuous concern around the world. Electrochemical energy has attracted much attention in replacing traditional fossil energy and promoting energy structure transformation due to its green, environmentally friendly, reliable and flexible characteristics. In recent years, a wide variety of electrochemical energy storage devices have been proposed and developed.

[0003] Among them, metallic zinc has a series of characteristics such as abundant resources, low cost, low electrochemical potential, large specific capacity and good environmental stability. In addition, aqueous electrolytes are environmentally friendly and highly safe. Therefore, rechargeable aqueous zinc batteries have great potential and can be used as the next generation of large-scale electrochemical energy storage devices.

[0004] In aqueous zinc-ion batteries with zinc as the negative electrode, the amount of charge carried by divalent zinc ions during the charging and discharging process doubles, and the battery has a large specific capacity. However, the zinc negative electrode of this system battery is prone to form dendrites during the charging process, resulting in low coulombic efficiency, rapid capacity decay, and the risk of short circuit in aqueous zinc batteries. In addition, due to the low redox potential of zinc, side reactions such as hydrogen evolution reactions will occur with the electrolyte, further reducing the coulombic efficiency. What's more, electronic insulating byproducts will passivate the surface of the zinc negative electrode, resulting in uneven current distribution, aggravating dendrite growth, and accelerating battery failure. Summary of the invention

[0005] The purpose of the present application is to overcome the above-mentioned deficiencies of the prior art and to provide an additive, an electrolyte and a battery to solve the technical problem of low battery performance caused by the existing electrolyte.

[0006] In order to achieve the above application purpose, the first aspect of the present application provides an additive which is pyridinium propane sulfonate, and the chemical formula of the pyridinium propane sulfonate is as follows:

[0007]

[0008] Compared with the prior art, this application has the following technical effects:

[0009] The additive provided by the present application, after being dissolved in the electrolyte, can be adsorbed on the negative electrode surface through pyridine and sulfonate polar functional groups, thereby forming an organic functional film layer. On the one hand, it can reduce the direct contact between the solvent water molecules in the electrolyte and the negative electrode surface, thereby effectively reducing or alleviating the hydrogen evolution corrosion and passivation reaction caused by solvent decomposition; on the other hand, it can regulate the diffusion pattern of cations on the electrode surface, induce regular and dense electrodeposition of cations, and therefore, with a greater probability, alleviate the formation and growth of dendrites due to uneven deposition of the cations, thereby improving the safety performance of the battery. At the same time, the sulfonate functional group can complex with the zinc cation, exclude the water molecules in the solvation sheath, and weaken the degree of side reactions. In summary, after using the above-mentioned additives, the performance of the battery is significantly improved.

[0010] In a second aspect of the present application, an electrolyte is provided, comprising an electrolyte salt, a solvent and the additives mentioned above.

[0011] The electrolyte provided in the present application, based on the above-mentioned additives, can significantly improve the performance and service life of the battery.

[0012] In a third aspect of the present application, a battery is provided, comprising the electrolyte described above.

[0013] The battery provided in the application, based on the above electrolyte, has a greatly improved service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0015] Figure 1 A schematic diagram of the charge and discharge cycle time of the battery of Examples 1 to 6 of the present application and Comparative Example 1 under the same test conditions;

[0016] Figure 2 A schematic diagram of the charge and discharge cycle time of the battery in Example 7 of the present application and Comparative Example 2 under the same test conditions;

[0017] Figure 3 A schematic diagram of the charge and discharge cycle time of the battery in Example 8 of the present application and Comparative Example 3 under the same test conditions;

[0018] Figure 4 Schematic diagram of the charge and discharge cycle time of the battery in Example 9 of the present application and Comparative Example 4 under the same test conditions. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0020] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0021] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0022] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0023] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0024] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0025] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0026] In a first aspect, an embodiment of the present application provides an additive, which is pyridinium propane sulfonate, and the chemical formula of pyridinium propane sulfonate is as follows:

[0027]

[0028] Pyridinium propanesulfonate (3-(1-Pyridinio)-1-propanesulfonate, PPS for short) is an organic molecule containing both polar functional groups pyridine and sulfonate ions. Therefore, at the zinc negative electrode-electrolyte interface, pyridine and sulfonate ions can be adsorbed together on the surface of the negative electrode plate, blocking the contact between water molecules in the electrolyte and the zinc negative electrode, thereby inhibiting hydrogen evolution corrosion and passivation reactions caused by water decomposition. At the same time, the diffusion pattern of zinc ions on the electrode surface is regulated to induce regular and dense electrodeposition, and the formation and growth of zinc dendrites are greatly reduced. Among them, the sulfonate ions can also complex with zinc ions, exclude water molecules in the solvation sheath, and weaken the degree of side reactions.

[0029] The additive provided in the present application contains pyridine and sulfonate polar functional groups, which can be adsorbed on the negative electrode surface through pyridine and sulfonate polar functional groups after being dissolved in the electrolyte, thereby forming an organic functional film layer. On the one hand, it can reduce the direct contact between the solvent in the electrolyte and the negative electrode surface, thereby effectively reducing or alleviating the hydrogen evolution corrosion and passivation reaction caused by solvent decomposition; on the other hand, it can regulate the diffusion pattern of cations on the electrode surface, induce regular and dense electrodeposition of cations, and therefore, with a greater probability, alleviate the formation and growth of dendrites due to uneven deposition of the cations, thereby improving the safety performance of the battery. At the same time, the sulfonate functional group can complex with zinc cations, exclude water molecules in the solvation sheath, and weaken the degree of side reactions. In summary, after using the above-mentioned additives, the performance of the battery is significantly improved.

[0030] Taking aqueous zinc batteries as an example, the negative electrode of the battery is metallic zinc, and the electrolyte also contains zinc ions. At the interface between the zinc negative electrode and the electrolyte, polar functional groups such as pyridine and sulfonate ions can be adsorbed on the surface of the negative electrode, blocking the contact between water molecules in the electrolyte and the zinc negative electrode, thereby inhibiting hydrogen evolution corrosion and passivation reactions caused by water decomposition. At the same time, the diffusion pattern of zinc ions on the electrode surface is regulated to induce regular and dense electrodeposition, and the formation and growth of zinc dendrites are greatly reduced. Furthermore, the polar functional group of the sulfonate group can also complex with zinc ions, excluding water molecules in the solvation sheath and weakening the degree of side reactions.

[0031] In a second aspect, an embodiment of the present application further provides an electrolyte solution including an electrolyte salt, a solvent and the above-mentioned additives.

[0032] Here, the electrolyte salt may be a soluble zinc salt.

[0033] The solvent may be ethylene carbonate, diethylene carbonate, dimethyl carbonate, ethylene glycol dimethyl ether, pure water, and the like.

[0034] Specifically, the electrolyte includes a soluble zinc salt, and the solvent includes water.

[0035] Among them, the soluble zinc salt specifically includes at least one of zinc sulfate, zinc chloride, zinc acetate, zinc bromide, zinc iodide, zinc fluoride, zinc formate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethylsulfonyl)imide, zinc perchlorate, zinc tetrafluoroborate, zinc nitrate, zinc methanesulfonate, zinc sulfamate, zinc gluconate, zinc lactate or zinc p-hydroxybenzenesulfonate.

[0036] For example, the electrolyte is prepared by mixing zinc sulfate and water; or, the electrolyte is prepared by mixing zinc acetate and water.

[0037] Specifically, the concentration of the soluble zinc salt in the electrolyte is 0.1 to 5.0 mol / L.

[0038] Optionally, the concentration of soluble zinc salt in the electrolyte may be 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, 1.9mol / L, 2.0mol / L, 3.0mol / L, 4.0mol / L, 5.0mol / L, etc.

[0039] Specifically, the concentration of the additive in the electrolyte is 1 to 500 mmol / L.

[0040] It will be appreciated that the additive is soluble in the solvent of the battery electrolyte.

[0041] Optionally, the concentration of the additive in the electrolyte may be 1mmol / L, 2mmol / L, 3mmol / L, 4mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L, 10mmol / L, 20mmol / L, 30mmol / L, 40mmol / L, 50mmol / L, 60mmol / L, 70mmol / L, 80mmol / L, 90mmol / L, 100mmol / L, 200mmol / L, 300mmol / L, 400mmol / L, 500mmol / L, etc.

[0042] Preferably, the concentration of the additive in the electrolyte is 5 mmol / L and 50-500 mmol / L.

[0043] In a third aspect, the present application also provides a battery, which includes an electrode assembly and the above-mentioned electrolyte. The electrode assembly includes a positive electrode sheet, a separator and a negative electrode sheet stacked in layers.

[0044] Of course, other necessary or auxiliary components are also included, such as a shell or an aluminum-plastic film, etc., which are used to encapsulate the electrode assembly and the electrolyte.

[0045] The battery provided in the embodiment of the present application has a significantly improved cycle life under the action of additives containing pyridine and sulfonic acid functional groups, and the battery performance is also significantly improved.

[0046] Specifically, the electrode assembly also includes other necessary or auxiliary components, such as a tab connected to the positive electrode sheet or the negative electrode sheet, and a shell for containing the electrode assembly. The diaphragm may be a glass fiber diaphragm, a polyolefin diaphragm, and a hydrogel diaphragm. The diaphragm is used to separate the positive electrode sheet and the negative electrode sheet to prevent a short circuit caused by direct contact between the two.

[0047] Specifically, the negative electrode plate is a zinc metal negative electrode plate.

[0048] Specifically, the positive electrode plate includes at least one of a manganese compound, a vanadium oxide, a Prussian blue analog, an organic polymer, activated carbon, copper, titanium, zinc, and stainless steel.

[0049] The following uses a number of specific embodiments to illustrate the application of the aqueous zinc battery electrolyte in the battery.

[0050] Battery Example:

[0051] Example 1

[0052] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 1 mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0 mol / L.

[0053] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and a certain amount of the above-mentioned aqueous zinc battery electrolyte is injected into the battery casing to complete the battery assembly.

[0054] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0055] Example 2

[0056] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 5mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0057] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0058] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0059] Example 3

[0060] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 10mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0061] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0062] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0063] Example 4

[0064] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 50mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0065] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0066] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0067] Example 5

[0068] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 100mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0069] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0070] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0071] Example 6

[0072] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 500mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0073] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0074] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0075] Example 7

[0076] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 5mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0077] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0078] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 20mA / cm 2 , the charge and discharge surface capacity is 20mAh / cm 2 .

[0079] Example 8

[0080] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 5mmol / L, and the concentration of zinc sulfate in the electrolyte is 2.0mol / L.

[0081] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0082] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 0.5mA / cm 2 , 1mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 , 20mA / cm 2 、30mA / cm 2 The battery was charged and discharged for eight cycles at each of the above charge and discharge current densities, and the charge and discharge surface capacity was 1 mAh / cm 2 After completion, the charge and discharge current density was maintained at 1 mA / cm 2 , the charge and discharge surface capacity is maintained at 1 mAh / cm 2 , and conduct long-term constant battery cycle charge and discharge test on the battery.

[0083] Example 9

[0084] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc acetate, and the additive is propane sulfonate pyridinium salt, and the two are dissolved in deionized water, wherein the concentration of propane sulfonate pyridinium salt in the electrolyte is 5mmol / L, and the concentration of zinc acetate in the electrolyte is 0.5mol / L.

[0085] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0086] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0087] Comparative Example 1

[0088] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, without additives, and the zinc sulfate is dissolved in deionized water, wherein the concentration of the zinc sulfate is 2.0 mol / L.

[0089] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0090] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0091] Comparative Example 2

[0092] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, without additives, and the zinc sulfate is dissolved in deionized water, wherein the concentration of the zinc sulfate is 2.0 mol / L.

[0093] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0094] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 20mA / cm 2 , the charge and discharge surface capacity is 20mAh / cm 2 .

[0095] Comparative Example 3

[0096] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc sulfate, without additives, and the zinc sulfate is dissolved in deionized water, wherein the concentration of zinc sulfate in the electrolyte is 2.0 mol / L.

[0097] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0098] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 0.5mA / cm 2 , 1mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 , 20mA / cm 2 、30mA / cm 2 The battery was charged and discharged for eight cycles at each of the above charge and discharge current densities, and the charge and discharge surface capacity was 1 mAh / cm 2 After completion, the charge and discharge current density was maintained at 1 mA / cm 2 , the charge and discharge surface capacity is maintained at 1 mAh / cm 2 , and conduct long-term constant battery cycle charge and discharge test on the battery.

[0099] Comparative Example 4

[0100] Prepare aqueous zinc battery electrolyte: the soluble zinc salt is zinc acetate, without additives, and the zinc acetate is dissolved in deionized water, wherein the concentration of zinc acetate is 0.5 mol / L.

[0101] Battery assembly: The zinc sheet is used as both the positive and negative electrode sheets of the battery, and the separator is a glass fiber separator. The positive electrode sheet, the glass fiber separator and the negative electrode sheet are stacked in sequence in the battery casing, and the same amount of the above-mentioned aqueous zinc battery electrolyte as in Example 1 is injected into the battery casing to complete the battery assembly.

[0102] Battery test: The battery is subjected to constant current cycle charge and discharge test, and the charge and discharge current density is 10mA / cm 2 , the charge and discharge surface capacity is 10mAh / cm 2 .

[0103] Each battery in Examples 1 to 9 and Comparative Examples 1 to 4 was tested under corresponding test conditions, and the test results are shown in Table 1 below:

[0104] Table 1

[0105]

[0106] Combining from Table 1 Figure 1 It can be seen that after adding additives to the electrolyte, the charge and discharge cycle time of the battery is greatly improved, especially in Examples 4 to 6, when the concentration of the additive is above 50 mmol / L, the charge and discharge cycle time of the battery reaches more than 200 h, while in Comparative Example 1, when there is no additive in the electrolyte, the charge and discharge cycle time of the battery is only 50 h, and a short circuit problem also occurs.

[0107] Combining from Table 1 Figure 2 It can be seen that when the charge and discharge current density in the test conditions of Example 7 is doubled, and the charge and discharge capacity is also doubled, the charge and discharge cycle time of the battery can also reach 100h, and no short circuit occurs. In Comparative Example 2, under the same test conditions as Example 4, the charge and discharge cycle time of the battery is only 36h, and short circuit occurs.

[0108] Combining from Table 1 Figure 3 It can be seen that when the test conditions in Example 8 are that the charge and discharge current densities are 0.5 mA / cm 2 , 1mA / cm 2 , 5mA / cm 2 , 10mA / cm 2 , 20mA / cm 2 、30mA / cm 2The battery was charged and discharged for eight cycles at each of the above charge and discharge current densities, and the charge and discharge surface capacity was 1 mAh / cm 2 After completion, the charge and discharge current density was maintained at 1 mA / cm 2 , the charge and discharge surface capacity is maintained at 1 mAh / cm 2 , and the battery was subjected to a long-term constant battery cycle charge and discharge test, and no short circuit phenomenon occurred for a long time. In Comparative Example 3, under the same test conditions as Example 5, although the battery can also be cycled at different charge and discharge current densities, a short circuit phenomenon occurred at about 75h in the long-term constant battery cycle charge and discharge test.

[0109] Combining from Table 1 Figure 4 It can be seen that in Example 9, when the soluble zinc salt is replaced with zinc acetate and the concentration of zinc acetate is reduced to 0.5 mol / L, the charge and discharge cycle time of the battery can also reach 50 hours, and no short circuit occurs. In Comparative Example 4, under the same test conditions as Example 6, the charge and discharge cycle time of the battery is only 25 hours, and short circuit occurs.

[0110] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An additive used in battery electrolyte, characterized in that: The additive is propane sulfonic acid pyridinium salt, and the chemical formula of the propane sulfonic acid pyridinium salt is as follows:

2. An electrolyte, characterized in that: The invention comprises an electrolyte salt, a solvent and the additive as claimed in claim 1.

3. The electrolyte according to claim 2, characterized in that: The concentration of the additive in the electrolyte is 1 to 500 mmol / L.

4. The electrolyte according to claim 2, characterized in that: The electrolyte salt includes a soluble zinc salt; the solvent includes at least one of water, ethylene carbonate, diethylene carbonate, dimethyl carbonate, and ethylene glycol dimethyl ether.

5. The electrolyte according to claim 4, characterized in that: The concentration of the soluble zinc salt in the electrolyte is 0.1-5 mol / L.

6. The electrolyte according to claim 4 or 5, characterized in that: The soluble zinc salt includes at least one of zinc sulfate, zinc chloride, zinc acetate, zinc bromide, zinc iodide, zinc fluoride, zinc formate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethylsulfonyl)imide, zinc perchlorate, zinc tetrafluoroborate, zinc nitrate, zinc methanesulfonate, zinc sulfamate, zinc gluconate, zinc lactate or zinc p-hydroxybenzenesulfonate.

7. A battery, characterized in that: Comprising the electrolyte as claimed in any one of claims 2 to 6.

Citation Information

Cited By

  • Aqueous zinc-ion battery electrolyte containing PLP additive, preparation method and battery

    CN122576436A